Hubungan Kemendagri dan Kemendes dalam Tata Desa dan Administrasi Desa - Sarip Sarip; Nur Rahman; Rohadi Rohadi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This article aims to explore the relationship between the Ministry of Home Affairs (Kemendagri) and the Ministry of Villages (Kemendes) from theconstitutional law and state administrative law point of view.The second concerns of this research is the disharmony and problem between the two ministries.From the constitutional law point of view, it turns out that what the Ministry of Home Affairs is doing, is closer to the object of its discussion. The method used in this research is normative legal research bycomparingthe constitutional law and state administrative law to obtain clarity regarding the Ministry of Home Affairs and Ministry of Village. The result shows that the Ministry of Village approached the science of state administrative law, namely to revive or give spirits to the village. Disharmonization began to exist since the inception of the Ministry of Village. The root of disharmony itself was the improper application of constitutional foundations in the formation of the Village Law. It would be better if the government reassess the constitutional foundation for the village.